EKSISTENSI SASTRA LISAN MAMACA DI KABUPATEN PAMEKASAN, MADURA - AM Hermien Kusmayati; Suminto A Sayuti (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to describe the existence and functions of the mamaca oral literaturein Pamekasan Regency, Madura. The data source was the “Rukun Sampurna” mamacaoral literature community in Jalmak Village, Pamekasan, Madura. The data were collectedthrough observations and interviews. They were analyzed by means of the emic and eticapproaches. These two approaches were simultaneously employed to attain the objectivityof research findings. The findings are as follows. First, the mamaca oral community isdeveloped by the “Rukun Sampurna” community through regular performances andfulfillment of the community’s requests or invitations for special events. Second, themamaca oral community stimulates the community to move to a better condition throughthe delivered messages. The audience will get inspiration for life spirit, optimism,enlightenment, and happiness.